Characterization of the mangrove swamp rice soils along the Great Scarcies River in Sierra Leone using principal component analysis - Baggie, I.; Sumah, F.; Zwart, Sander J.; Sawyerr, P.; Bandabla, T.; Kamaraa, C.S. (Elsevier, 2018)
Mangrove swamp rice cultivation is important for food security in some countries of West Africa including Sierra Leone. In this agro-ecology, rice is cultivated during the rainy season when freshwater flows in the rivers and salt and acidity concentrations have reduced to non-toxic levels. Rice yields in the mangrove ecosystem of Sierra Leone are higher than in other agro-ecologies and weed, disease and pest pressures are minimal. However, salinity, acidity and crabs negatively affect rice productivity in the mangrove swamps. Due to the differences in levels of flooding, salinity and acid sulphate conditions of mangrove swamp soils, it is assumed that there is variability of soil properties of mangrove swamps along the associated river, which may impact the choice of suitable rice varieties and soil management practices. The purpose of this study was to understand the soil physical and chemical properties of mangrove swamp soils along the Great Scarcies River of Sierra Leone. A soil sampling survey was designed and implemented using transects to collect composite soil samples of 1 ha area at 0–0.2 m depth at 11 different sites located from the estuary of the Great Scarcies River to approximately 35 km inland. The soil samples were air-dried, processed and analyzed for selected physical and chemical properties by recommended methods. Statistical analysis generated mean, standard deviations, coefficient of variation, correlation matrix and principal components. The high variability in soil physical and chemical characteristics of mangrove swamp soils along the Great Scarcies River could be attributed to the complex interactions between the twice daily tidal inundations and depositions of soil organic matter, physical particles and nutrients onto the mangrove swamp soils along the river. The result of this is a soil fertility gradient down-stream.